Tragedi dan Romantisme dalam Film “Kupu-Kupu Kertas” - Bariroh, Rusydah; Mardiningsih, Mardiningsih; Rosidah, Ilmiyatur (Universitas Negeri Padang, 2025)
Film as an audiovisual work of art not only conveys a story, but also contains various layers of meaning that can be analyzed through a semiotic approach. This article aims to reveal the meaning of tragedy and romance in the film “Kupu-Kupu Kertas” through Roland Barthes' semiotic theory which includes three layers of meaning: denotative, connotative, and myth. This study uses a qualitative descriptive. The results of the analysis show that the tragedy in this film is depicted through the main character's inner conflict, sacrifice, and sad fate, while romance is reflected in deep emotional relationships and idealistic values of love. These two aspects not only form the narrative structure of the film, but also represent social and ideological values that live in society.